COVID-19 Impairs Immune Response to Candida albicans - Moser, Dominique; Biere, Katharina; Han, Bing; Hoerl, Marion; Schelling, Gustav; Choukér, Alexander; Woehrle, Tobias (Frontiers in Immunology, 2021)
Infection with SARS-CoV-2 can lead to Coronavirus disease-2019 (COVID-19) and result in severe acute respiratory distress syndrome (ARDS). Recent reports indicate an increased rate of fungal coinfections during COVID-19. With incomplete understanding of the pathogenesis and without any causative therapy available, secondary infections may be detrimental to the prognosis. We monitored 11 COVID-19 patients with ARDS for their immune phenotype, plasma cytokines, and clinical parameters on the day of ICU admission and on day 4 and day 7 of their ICU stay. Whole blood stimulation assays with lipopolysaccharide (LPS), heat-killed Listeria monocytogenes (HKLM), Aspergillus fumigatus and Candida albicans were used to mimic secondary infections, and changes in immune phenotype and cytokine release were assessed. COVID-19 patients displayed an immune phenotype characterized by increased HLA-DR+CD38+ and PD-1+ CD4+ and CD8+ T cells, and elevated CD8+CD244+ lymphocytes, compared to healthy controls. Monocyte activation markers and cytokines IL-6, IL-8, TNF, IL-10 and sIL2Rα were elevated, corresponding to monocyte activation syndrome, while IL-1β levels were low. LPS, HKLM and Aspergillus fumigatus antigen stimulation provoked an immune response that did not differ between COVID-19 patients and healthy controls, but COVID-19 patients showed an attenuated monocyte CD80 upregulation and abrogated release of IL-6, TNF, IL-1α and IL-1β towards Candida albicans. This study adds further detail to the characterization of the immune response in critically ill COVID-19 patients, and hints at an increased susceptibility for Candida albicans infection.